Use of COVID-19 personal protective equipment pollutants to improve physical properties of silty sand in Yellow River flooded area - Wang, Hao; Guo, Jianbo; Liu, Weiwei; Song, Haoming; Yan, Tiantian; Fu, Dewei (Frontiers in Environmental Science, 2022)
Silty sand in the Yellow River flood area (YRFA) of China exhibits a low cohesive force and water-holding capacity. Its direct use for subgrade filling leads to phenomena such as subgrade bed depression, slurry, and mud. Therefore, from the perspective of waste utilization, this study investigates disposable protective clothing (DPC) and disposable nitrile gloves (DNG) produced due to COVID-19 in combination with silty sand as subgrade filling for the YRFA. Through an unconfined compressive strength and permeability test, we studied the influence of personal protective equipment (PPE) with different moisture content, concentration, and size on the strength and permeability of mixed samples. Further, we discuss its impact on the improvement of subgrade filling in YRFA. Results show that adding DPC improves both the compressive strength and ductility of the sample. However, the impermeability of the sample remains unchanged. In contrast, the addition of DNG does not increase the unconfined compressive strength and ductility of the sample, whereas it significantly improves its impermeability. The size of PPE has a considerable influence on the compressive strength of the mixed sample, whereas it does not affect the sample permeability. This method makes use of the PPE waste produced due to COVID-19, reduces environmental pollution, and provides a novel concept for improving silty sand in the YRFA.